Principles of micro-economics - Frank, Robert H. (McGraw-Hill / Irwin, 2004)
Based on reviewer feedback, this edition offers (1) even more streamlined coverage of the cost-benefit approach in the introductory chapter; (2) exercises that are more closely tied to the examples; (3) expanded narrative explanations of important principles, making them more accessible to average students; and (4) expanded coverage of several key topics [see below]. The result is a revision that is motivating to students, an effective text for teaching, and an exciting first course in Economics.